2022
DOI: 10.1001/jamapediatrics.2022.0710
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive High-Frequency Oscillatory Ventilation vs Nasal Continuous Positive Airway Pressure vs Nasal Intermittent Positive Pressure Ventilation as Postextubation Support for Preterm Neonates in China

Abstract: for the Nasal Oscillation Post-Extubation (NASONE) Study Group IMPORTANCE Several respiratory support techniques are available to minimize the use of invasive mechanical ventilation (IMV) in preterm neonates. It is unknown whether noninvasive high-frequency oscillatory ventilation (NHFOV) is more efficacious than nasal continuous positive airway pressure (NCPAP) or nasal intermittent positive pressure ventilation (NIPPV) in preterm neonates after their first extubation.OBJECTIVE To test the hypothesis that NHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 48 publications
3
47
0
Order By: Relevance
“…We speculate that the direction of results would be similarly favourable for nHFOV in less stable infants. In fact, a recent large multicentre trial demonstrated that nHFOV used as post-extubation respiratory support reduced duration of mechanical ventilation compared with nCPAP or non-invasive intermittent positive pressure ventilation 31. Second, EIT data only show relative changes rather than absolute lung volumes.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the direction of results would be similarly favourable for nHFOV in less stable infants. In fact, a recent large multicentre trial demonstrated that nHFOV used as post-extubation respiratory support reduced duration of mechanical ventilation compared with nCPAP or non-invasive intermittent positive pressure ventilation 31. Second, EIT data only show relative changes rather than absolute lung volumes.…”
Section: Discussionmentioning
confidence: 99%
“…17 Zhu et al included in their study 1440 very preterm infants to test the success of various modalities to prevent from re-intubation and found that re-intubation was lower in infants receiving nHFOV when compared to nCPAP. 9 In a metaanalysis investigating the use of nHFOV and nCPAP as primary respiratory support in RDS, it was found that nHFOV reduced the intubation rate. 18 In the present study, we also focused on secondary complications that may be related to non-invasive positive pressure ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…8,19,20 Consistent with recent studies, we found that air leak syndrome was similar between the nHFOV and nCPAP groups. 9,[14][15][16][17] Compared to nCPAP, studies have shown that nHFOV does not further increase the risk of bronchopulmonary dysplasia, necrotizing enterocolitis, intraventricular hemorrhage, retinopathy of prematurity, and pulmonary hemorrhage. 9,[13][14][15][16] Similar to our results, other studies have found no difference in mortality between nH-FOV and nCPAP groups in the preterm population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations